EFFECTIVENESS OF EXISTENTIAL GROUP THERAPY FOR TREATMENT OF PSYCHOLOGICAL PROBLEM OF CERVICAL CANCER PATIENTS - ADMASU, S.Y.; Vagrecha, Y.s.; ENDALEW, M.S. (Innovare Journal of Social Sciences, 2015)
ABSTRACT Background: Cervical cancer or cancer of cervix is one of just a few cancers caused by a virus. The virus, called Human Papilloma Virus (HPV) can infect a woman's cervix when she has sex. Now a days the prevalence of it is evidenced that approximately 83% of the world's new cases and 85% of all cervical cancer deaths reported are from developing countries. Objective: This study examined the effectiveness of Existential Group Therapy in treating psychological problem (Depression) among patient with cervical cancer in Ethiopia. Method: The study was a non-equivalent control group pretest-posttest, quasi-experimental design. Thirty research participants were selected purposefully based on inclusion criteria. They were divided in to two groups (psychotherapeutic group and control group). Standard scale namely, Beck Depression Inventory II, were used to measure the dependent variables at two occasions; pre-test and post-test. Research participants in the psychotherapeutic group received Existential Group therapy for nine sessions; three sessions per week for ninety minutes of each session. Result: Result of dependent t-test illustrated that, after treatment, research participants engaged in psychotherapeutic group showed statistically significant reduction in the level of Depression compare to the control group. Key Words: Cervical cancer, Depression, Existential Group Therapy Â 